Theories of Normative Ethics and Ehical Challenges in the Field of Information Management - M Khandan (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2010)
Objective: Current ethical issues in information management are examined from the stand point of four major normative ethics theories (consequence-based, duty-based, right-based and virtue-based). Methodology: A conceptual analysis method was used. Findings : By offering a discourse on the definition and division of ethics, history of information ethics and its principle topics, the present paper illustrates substantiatively that from what standpoint does each of the ethical theories posits major ethical issues in information management